Bebas Stunting Melalui Melek Informasi Kesehatan dan Mandiri Pangan Berbasis Teknologi pada kelompok Ibu- ibu Posyandu Kampung Komra - Hendry Kiswanto Mendrofa; Elisabeth Bre Boli; Lalu Panji Iman Agamawan; Khairunisa Kartika; Yukiur Wenda (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Based on data from the Sarmi District Health Office in 2023, the prevalence of stunting among children under five reached 22.5%, spread across 11 community health centers. This figure remains far above the national target of 14%, necessitating intensive efforts to reduce it. In 2024, a study conducted by nursing students at Cenderawasih University revealed that in the Betaf health center area, 21.2% (55 out of 259) of children under five were stunted. Additionally, the Betaf health center reported that Kampung Komra itself recorded 15 cases of stunting in 2023. The high prevalence of stunting in this area has motivated the team to implement a community partnership program aimed at empowering Posyandu mothers, who play a crucial role in health and nutrition education for pregnant women and young children. This community service program aims to reduce stunting rates in Kampung Komra through health education, strengthening food independence with the implementation of Sustainable Food House Areas (KRPL), aquaponics-based fish farming, and the use of information technology in stunting prevention. Nutritional status measurements of children under five in the Posyandu of Kampung Komra indicate that 35% are stunted, underscoring the need for continuous interventions to meet the nutritional needs of pregnant women, breastfeeding mothers, and young children.Given the high stunting rate and the community's limited ability to independently meet their food needs, this program should be continued periodically. Additionally, the program should be supported with intensive training for Posyandu mothers and access to affordable food resources, considering the community's preference for hunting over livestock farming, low economic conditions, and high commodity prices.